Characterization of carbon/glass hybrid unidirectional thermoplastic composite. (2021) - Maier, Andreas; Staudt, Bernhard; Kroll, Lothar
Abstract: A tailored use of continuous fibre-reinforced plastics in the so called "skeleton design" enables their application in high volume car body structures. Unidirectional profiles with a cross-section of 10 mm × 10 mm made of Polyamide 6 with four different carbon/glass fibre ratios were characterized in fully dried state. Flexural modulus, strength and strain to failure of profiles were determined using a four-point bending test as comparative testing method. Results are investigated regarding the effect of hybridization on mechanical properties. Flexural modulus and strain to failure show strong dependency on geometrical placement of fibres and fibre fraction of carbon fibres. A positive hybrid effect, defined as the deviation from rule of mixture, could not be identified regarding the investigated hybrid configurations. It is shown that mechanical properties of profiles can be customized by adjusting the carbon/glass ratio as well as the spatial arrangement of fibres to meet structural requirements.